Color y experiencia, lenguaje y arte - Iribas Rudín, Ana (Arte, Individuo y Sociedad, 2007)
This article is about the language used to describe the subjective experience of colour and deals with two special types of experience, achromatopsia and synaesthesia. Both are briefly described from the point of view of neurophysiology, and, in greater extent, phenomenologically. Examples are offered of these particulars in relation to visual art.
Keywords: Perception; Experience; Qualia; Achromatopsia; Synaesthesia; Language; Visual art